2019
DOI: 10.1177/0960327119874428
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium supplementation ameliorates toxic effects of 2,4-dichlorophenoxyacetic acid in rat model

Abstract: 2,4-Dichlorophenoxyacetic acid (2,4-D) is an extensively used herbicide in the field of agriculture, its ever-escalating use induces toxicity, health effects, and environmental impact. Oxidative stress plays a key role in pathogenesis of 2,4-D-induced liver and kidney damage. Magnesium (Mg) is a highly effective antioxidant agent in restoring oxidative damage by directly influencing the metabolic and physiological processes. Therefore, the present study aimed to evaluate Mg role in ameliorating the oxidative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
3
9
0
1
Order By: Relevance
“…It has been estimated that it is the fourth most abundant cation in the whole body and the second at the intracellular level [3,4]. Magnesium is an essential co-factor in the enzymatic pathways involved with energy, protein and lipid metabolism and the modulation of glucose transport through the cellular membrane [5][6][7][8]. Thus, magnesium serves as an important link between transport systems and metabolism, and its concentration in the cytoplasm is regulated in a highly precise manner [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that it is the fourth most abundant cation in the whole body and the second at the intracellular level [3,4]. Magnesium is an essential co-factor in the enzymatic pathways involved with energy, protein and lipid metabolism and the modulation of glucose transport through the cellular membrane [5][6][7][8]. Thus, magnesium serves as an important link between transport systems and metabolism, and its concentration in the cytoplasm is regulated in a highly precise manner [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed in rats receiving doses of 5 mg/kg of Désormone Lourd (600 g/L 2,4-D) for 4 weeks, resulting in a decrease in hepatic GSH levels and the activity of SOD, CAT, GPx, and GST [ 33 ]. Toxicity studies conducted with the active ingredient in rats identified similar results, further supporting that this effect is attributed to the active ingredient [ 71 , 74 ].…”
Section: Resultsmentioning
confidence: 64%
“…Exposure to 2,4-D also leads to the depletion of GSH levels in the liver, contributing to a decrease in antioxidant capacity [ 71 , 119 ]. This effect was observed in rats receiving doses of 5 mg/kg of Désormone Lourd (600 g/L 2,4-D) for 4 weeks, resulting in a decrease in hepatic GSH levels and the activity of SOD, CAT, GPx, and GST [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various experimental evidence explains magnesium's antioxidant and defensive role against some toxic substances ( 34 , 35 ), which may imply the importance of magnesium in restoring oxidative damage provoked by pesticides. Furthermore, Shafeeq and Mahboob's study in a rat model found that magnesium supplementation ameliorated the toxicity of 2,4-dichlorophenoxyacetic acid ( 36 ). As is known, magnesium sulfate is used to reverse pesticide poisoning.…”
Section: Discussionmentioning
confidence: 99%